C-N coupling reactions of allenes and methylacetylenes with an imidotitanium complex - Trosch, D; Collier, P; Bashall, A; Gade, L; McPartlin, M; Mountford, P; Radojevic, S (2001)
Reaction of the imidotitanium complexes [(N 2Npy-κ 3N)Ti(-NtBu)(py)] (1) and [(N 2Npy-κN)Ti(=NtBu)] (1a) (N 2Npy = (2-C 5H 4N)C(Me)CH 2NSiMe 3) 2 ) with 2-butyne and 1-phenyl-propyne led to C-N coupling with the imido ligand and yielded the four-membered titanaazetidines [(N 2Npy-κ 3N)Ti{N(tBu)C(CHCH 3) CH 2}] (2) and [(N 2Npy-κ 3N)Ti{N(tBu)C-(CHC 6H 5 )CH 2}] (3), respectively. The same reaction products were obtained in 2 + 2 cycloaddition reactions of 1 and 1a with 1,2-butadiene and phenylallene. The four-membered metallacycle with an exocyclic C=C double bond was established by X-ray diffraction studies of both compounds. A mechanism to explain the observed products from both types of reactions is proposed. Whereas the reactions of 1 with CO 2, tBuNCO, and PhNCO were highly unspecific and did not lead to an isolable product, the conversion with the sterically encumbered isocyanate 2,6-iPr 2C 6H 3NCO yielded the product of 2 + 2 cycloaddition to the Ti=N bond, namely [(N 2Npy-κ 3N)Ti{N(tBu)C(N-2,6-C 6 H 3iPr 2)O}(py)] (4), the structure of which was elucidated by NMR spectroscopy.